The Patient Perspective on Errors in Cancer Care: Results of a Cross-Sectional Survey. Issue 4 (December 2019) - Carey, Mariko; Boyes, Allison W.; Bryant, Jamie; Turon, Heidi; Clinton-McHarg, Tara; Sanson-Fisher, Robert
Abstract : Objective: The objective of this study was to explore medical oncology outpatients' perceived experiences of errors in their cancer care. Methods: A cross-sectional survey was conducted. English-speaking medical oncology outpatients aged 18 years or older were recruited from 9 Australian cancer treatment centers. Participants completed 2 paper-and-pencil questionnaires: an initial survey on demographic, disease and treatment characteristics upon recruitment; and a second survey on their experiences of errors in cancer care 1 month later. Results: A total of 1818 patients (80%) consented to participate, and of these, 1136 (62%) completed both surveys. One hundred forty-eight participants (13%) perceived that an error had been made in their care, of which one third (n = 46) reported that the error was associated with severe harm. Of those who perceived an error had been made, less than half reported that they had received an explanation for the error (n = 65, 45%) and only one third reported receiving an apology (n = 50, 35%) or being told that steps had been taken to prevent the error from reoccurring (n = 52, 36%). Patients with university or vocational level education (odds ratio [OR] = 1.6 [1.09–2.45], P = 0.0174) and those who received radiotherapy (OR = 1.72 [1.16–2.57]; P = 0.0076) or "other" treatments (OR = 3.23 [1.08–9.63]; P = 0.0356) were significantly more likely to report an error in care. Conclusions: There is significant scope to improve communication with patients and appropriate responses by the healthcare system after a perceived error in cancer care.